Heme oxygenase 1-generated carbon monoxide and biliverdin attenuate the course of experimental necrotizing pancreatitis - Nuhn, Philipp; Bergmann, Frank; Fischer, Lars; Giese, Nathalia (Pancreas, 2013)
The cytoprotective enzyme heme oxygenase 1 (HO-1) is highly up-regulated in acute pancreatitis (AP). In this study, we tested its metabolites as potential therapeutic agents for AP in rats.